Environmental attitudes of Chinese students in higher education institutions - Yue, Xiaoyao; Wanglee, Weichi; Yin, Ying; Ye, Yan; Cai, Ting (Journal of Education and e-Learning Research, 2023)
This study investigates the influence of environmental attitudes of Chinese students in higher education institutions (HEIs). It included 988 students at ten higher education institutions and administered an “environmental attitudes inventory" questionnaire to investigate gender, grade level of study, institution level, parental educational background, scholarships, annual household income, students' leadership experience and the extent to which variables such as participation in environment-related courses affect students' attitudes towards the environment. Furthermore, the study relied on descriptive and analytical methods. The results show significant differences in grade, school level and parents' educational backgrounds on students' environmental attitudes. In contrast, gender, scholarship, annual family income and student leader experience related to the environment did not appear as significant factors. This paper suggests that education policymakers incorporate these influences into a vision of environmental educational reform to inform the remedial actions needed by higher education institutions.